Improved Thermal Stability of Al-Si Alloy Coated Steel Sheet with Cr Thin Film Deposition - Jae-Hyeon Kim; Jung-Ha Lee; Seung-Beop Lee; Sung-Jin Kim; Min-Suk Oh (Archives of Metallurgy and Materials)
We investigated the effect of Cr thin film deposition on the thermal stability and corrosion resistance of hot-dip aluminized steel. A high-quality Cr thin film was deposited on the surface of the Al-9 wt. % Si-coated steel sheets by physical vapor deposition. When the Al-Si coated steel sheets were exposed to a high temperature of 500℃, Fe from the steel substrate diffused into the Al-Si coating layer resulting in discoloration. However, the highly heat-resistant Cr thin film deposited on the Al-Si coating prevented diffusion and surface exposure of Fe, improving the heat and corrosion resistances of the Al-Si alloy coated steel sheet.